2021
DOI: 10.3390/life11070651
|View full text |Cite
|
Sign up to set email alerts
|

Study of Skin Barrier Function in Psoriasis: The Impact of Emollients

Abstract: Psoriasis is a chronic multi-systemic inflammatory disease that affects the epidermal barrier. Emollients can be used as a coadjutant therapy for psoriasis management, but little is known about how the epidermal barrier function in psoriatic patients is modified by moisturizers. The objective of this study is to evaluate the effect of Vaseline jelly and a water-based formula on epidermal barrier function in psoriatic patients. Thirty-one patients with plaque-type psoriasis and thirty-one gender and age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(49 reference statements)
0
24
0
3
Order By: Relevance
“…Emollients restore physical barrier function by forming a lipid-rich layer that prevents water loss from the skin, and by facilitating water binding in the stratum corneum [ 241 ]. Their application to psoriatic plaques reduces transepidermal water loss, plaque scaling and pruritis, and also normalises epidermal markers of differentiation and proliferation [ 242 , 243 ]. Emollients are particularly used in conjunction with topical steroid therapy, as they increase drug penetration [ 242 ].…”
Section: Psoriasis Current Treatment and Future Directionsmentioning
confidence: 99%
“…Emollients restore physical barrier function by forming a lipid-rich layer that prevents water loss from the skin, and by facilitating water binding in the stratum corneum [ 241 ]. Their application to psoriatic plaques reduces transepidermal water loss, plaque scaling and pruritis, and also normalises epidermal markers of differentiation and proliferation [ 242 , 243 ]. Emollients are particularly used in conjunction with topical steroid therapy, as they increase drug penetration [ 242 ].…”
Section: Psoriasis Current Treatment and Future Directionsmentioning
confidence: 99%
“…Emollients are recommended in guidelines for treating psoriasis 23 . Recently, a study reported a beneficial effect of emollients on skin barrier function in psoriatic skin 24 . Here, we show that emollients alone can decrease the immune infiltrate (mostly CD8+ cells) in the dermis after only 4 weeks of applications.…”
Section: Discussionmentioning
confidence: 47%
“…It has been reported that through hydrating the stratum corneum, emollients enhance the absorption of topical corticosteroids [8]. Moreover, research demonstrates that use of emollients decreases transepidermal water loss in psoriatic patients [9], which is usually high due to lesions characterized by a damaged skin barrier.…”
Section: Discussionmentioning
confidence: 99%